Bapemperda’s Strategy for Enhancing the Quality and Effectiveness of Regional Regulations - Ali Rahmat; Tuti Widyaningrum (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The performance of the Regional Regulation Formation Agency (Bapemperda) plays a crucial role in producing high-quality Regional Regulations as instruments of regional autonomy. This study aims to analyze the performance of Bapemperda within the Regional House of Representatives (DPRD) of West Kotawaringin Regency and to identify efforts to enhance its effectiveness in the formulation and oversight of Regional Regulations. This research employs an empirical juridical method with a normative approach, utilizing interviews, observations, and document analysis as data collection techniques. The findings indicate that Bapemperda’s performance is relatively effective; however, it continues to face challenges related to supervisory functions, limited public participation, and resource constraints. Efforts to address these challenges include strengthening human resource capacity, improving institutional coordination, conducting systematic evaluations of Regional Regulations, and increasing community engagement. In conclusion, institutional strengthening and the optimization of legislative and oversight functions are essential for enhancing the quality of responsive and effective Regional Regulations.